Mitigation of Voltage Fluctuation in Power Distribution System Using D-STATCOM - Yahia M Esmail; S K Elsayed; M A Mehanna (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Electrical Power Quality is becoming intensity concerned from both electric utilities and customers. Voltage Fluctuations is a major power quality problem as it has a significant impact on both the equipment and production environment. This work describes the voltage control technique of mitigation of voltage fluctuations and clearing fault using Distribution Static Synchronous Compensator (DSTATCOM). The test system used is IEEE 9-bus distribution system clarified optimal location of DSTATCOM by using Artificial Neural Network (ANN). A simulation was done using MATLAB/Simulink software to obtain the results.